On the equality of Real Interest Rates across borders in Integrated Capital Markets - Patrick Minford; David Peel (Cardiff University, Cardiff Business School, 2005)
The purpose in this letter is first to review briefly the empirical results on the relationship between real interest rates and real exchange rates; this empirical literature provides little support for the hypothesis of Roll that expected real interest rates are equal in general. Our second aim is to discuss the theoretical conditions that have to be met for his hypothesis to hold.
Keywords: F31; C22; C51; 330; Real interest rates; Real Exchange rates; Roll